StructureActivity Relationship Study of Xanthoxyline and Related Small Methyl Ketone Herbicides - Warot Chotpatiwetchkul; Nawasit Chotsaeng; Chamroon Laosinwattana; Patchanee Charoenying (My University, 2022)
Xanthoxyline (1), a small natural methyl ketone, was previously reported as a plant growth inhibitor. In this research, related methyl ketones bearing electron-donating and electron-withdrawing groups, together with heteroaromatics, were investigated against seed germination and seedling growth of Chinese amaranth (Amaranthus tricolor L.) and barnyard grass [Echinochloa crus-galli (L.) Beauv]. The structure-activity relationships (SARs) of methyl ketone herbicides were clarified, and which types and positions of substituents were crucially important for activity were also clarified. Indole derivatives, namely, 3-acetylindole (43) and 3-acetyl-7-azaindole (44) were found to be the most active methyl ketones that highly suppressed plant growth at low concentrations. The molecular docking on the 4-hydroxyphenylpyruvate dioxygenase (HPPD) enzyme indicated that carbonyl, aromatic, and azaindole were key interactions of HPPD inhibitors. This finding would be useful for the development of small ketone herbicides.
Keywords: Methyl Ketone; Docking (animal); Allelopathy and phytotoxic interactions